Desenvolvimento de uniformes escolares segundo as propriedades do design - Herrera, Rafaeli Fernanda (2011)
This research seeks to elucidate important considerations relevant to the development and design of school uniforms,focusing main properties of design and materials commonly used in this product segment and also the suggestion of technological materials available that are not yet employed in school clothing.